Effect of dietary essential fatty acids on level of oestradiol‐17β and vitellogenin, reproductive performance and larval quality of striped catfish (Pangasianodon hypophthalmus) in out‐of‐spawning season. (17th June 2020) - Pamungkas, Wahyu; Jusadi, Dedi; Zairin, Muhammad; Setiawati, Mia; Supriyono, Eddy; Imron, Imron
Abstract: A study was conducted to determine the effect of essential fatty acid in striped catfish (Pangasianodon hypophthalmus) broodstock diets on a level of oestradiol‐17β and vitellogenin, reproductive performance and larval quality in out‐of‐spawning season. Five female and five male broodstock were stocked into a net cage (3 × 5 × 1.5 m 3 ) and fed with pelleted diets containing 1.5% fish oil and different amounts of corn oil (CO) in diet formulation, that is 0%, 1%, 2% and 3% respectively. Gonadal development, oestradiol‐17ß and vitellogenin concentrations were examined every 2 weeks. Oestradiol‐17ß and vitellogenin concentrations showed an increase during the maturation process. The significantly highest percentage of female mature, fecundity, hatching rate, larval production and larval survival rate were obtained from fish fed with 2% corn oil in the diet. This result revealed that the administration of 2% corn oil in the diet as a source of n‐6 (linoleic acid) and 1.5% fish oil as a source of n‐3 (linolenic acid) can improve the reproductive performance of striped catfish broodstock in out‐of‐spawning season.